Fiscal policy and inflation: Understanding the role of expectations in Mexico - Bernabe Lopez-Martin; Alberto Ramírez de Aguilar; Daniel Sámano (Banco de México, 2018)
This paper estimates a hidden Markov model where inflation is determined by government deficits financed through money creation and by expectations dynamics. The baseline model, proposed by Sargent et al. (2009) is able to distinguish between causes and remedies of hyperinflation, such as persistent or transitory shocks to fiscal deficits, and the de-anchoring of inflation expectations. The estimated sequence of monetized deficits provides an adequate account of inflation for the period 196994. The paper then extends the model to analyze the possibility that fiscal policy can affect inflation expectations in a context of Central Bank independence, as is the case of Mexico after 1994. Evidence is found that the exchange rate and sovereign interest rate spreads influence the evolution of inflation.
Keywords: E31; E42; E52; E63; 330; Inflation; Inflation Expectations; Fiscal Deficit